Pengaruh Produksi Dan Luas Lahan Terhadap Ekspor Teh Di Indonesia - Putri Sara Purba; Reza Juanda; Tarmizi Abbas; Devi Andriyani (LPPM Universitas Malikussaleh - Indonesia, 2023)
This study aims to analyze the effect of production and land area on tea exports in Indonesia. The independent variables include production and land area while the dependent variable includes exports. The data used in this research is secondary data during the 2006-2020 period. The regression model used in this study is a multiple linear regression model with the Ordinary Least Square (OLS) method. This study uses classical assumption tests such as the normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. Based on the results of the study, it shows that tea production has a positive and significant effect on tea exports in Indonesia, while land area has a positive and insignificant effect on tea exports in Indonesia. The test results for the coefficient of determination show that there is a relationship between the independent variables and the dependent variable in this study of 78.39%, which means that the other 21.60% is influenced by other variables outside of this study.